Versatile multilinked aerial robot with tilted propellers: Design, modeling, control, and state estimation for autonomous flight and manipulation. Issue 7 (25th May 2021) - Zhao, Moju; Anzai, Tomoki; Shi, Fan; Maki, Toshiya; Nishio, Takuzumi; Ito, Keita; Kuromiya, Naoki; Okada, Kei; Inaba, Masayuki
Abstract: A multilinked structure can benefit aerial robots in terms of both maneuvering and manipulation owing to its ability of aerial transformation. A coplanar multilinked model was developed in our previous study. However, the maneuvering and manipulation performances of that model were limited owing to the weak controllability. Therefore, we adopt tilted propellers in this study to enhance controllability. The related design, modeling, and control method are developed to achieve stable hovering and transformation with tilted propellers. Further, state estimation which involves time synchronization between sensors and multilinked kinematics is also presented in this study to enable fully autonomous flight in outdoor environments. The experimental evaluation of the design, modeling, and control method is performed to verify stability during aerial transformation. While, various autonomous outdoor experiments including trajectory following, fast maneuvering for intercepting a target, object grasping for delivery, and blanket manipulation for firefighting are also performed to verify the versatility of the proposed robot platform. To the best of our knowledge, this is the first study of a multilinked aerial robot that can achieve fully autonomous flight and manipulation tasks in an outdoor environment. We also applied our platform in all challenges of the 2020 Mohammed Bin Zayed International Robotics Competition, and we ranked in the third place in Challenge 1 and in the sixth place in Challenge 3 internationally, thereby demonstrating the reliable flight performance in the fields.